2001
DOI: 10.3904/kjim.2001.16.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Forced Oscillation Techniques FOT in patients with Bronchial Asthma

Abstract: Background:Forced oscillation technique (FOT) is a method to characterize the mechanical properties of the respiratory system over a wide range of frequencies. Its’ most important advantage is to require minimal cooperation from the subject. This study was performed to evaluate the usefulness of the FOT applications in patients with bronchial asthma by estimating the associations between asthma severity and FOT parameters, and the relationships between FOT and spirometry parameters.Methods:216 patients with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
3
17
0
3
Order By: Relevance
“…Goldman et al (36) proposed that the integrated X over a range of low frequencies (5 Hz to F res ) provides meaningful evidence of airflow obstruction beyond the sensitivity of spirometry. Still others have shown that F res correlates best with baseline FEV 1 (r=-0.55) (28). Schmekel and Smith (31) found that the change in F res following EVH correctly diagnosed asthma with 89% sensitivity and 100% specificity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Goldman et al (36) proposed that the integrated X over a range of low frequencies (5 Hz to F res ) provides meaningful evidence of airflow obstruction beyond the sensitivity of spirometry. Still others have shown that F res correlates best with baseline FEV 1 (r=-0.55) (28). Schmekel and Smith (31) found that the change in F res following EVH correctly diagnosed asthma with 89% sensitivity and 100% specificity.…”
Section: Discussionmentioning
confidence: 97%
“…Debate exists concerning which is more discriminating when detecting airway obstruction; however, it is widely accepted that IOS measurements are frequency-dependent with the pronounced changes occurring at lower frequencies (24,25,38,39). Some studies have shown that resistance at 5 Hz significantly correlates with baseline FEV 1 (26,28), postmethacholine challenge FEV 1 (25,27,32) or postbronchodilator FEV 1 values (24,33,38). Others have suggested that X at 5 Hz is most sensitive to changes in airway calibre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced oscillometry has been used to demonstrate airway obstruction and response to bronchodilation and challenge tests in asthma . There is evidence that this method is more sensitive than spirometry in asthma, but also that it has greater variability, especially with regard to reactance measures .…”
Section: Introductionmentioning
confidence: 99%
“…15 Forced oscillometry has been used to demonstrate airway obstruction and response to bronchodilation and challenge tests in asthma. [16][17][18][19] There is evidence that this method is more sensitive than spirometry in asthma, but also that it has greater variability, especially with regard to reactance measures. 20,21 Forced oscillometry can assess both overall and peripheral airway mechanics by utilizing low frequencies that travel all the way to the small airways and, thus, reflect the whole airway tree and high frequencies that travel only proximally, mainly reflecting central airways.…”
mentioning
confidence: 99%